2013
DOI: 10.1261/rna.039164.113
|View full text |Cite
|
Sign up to set email alerts
|

Emerging complexity of the HuD/ELAVl4 gene; implications for neuronal development, function, and dysfunction

Abstract: Precise control of messenger RNA (mRNA) processing and abundance are increasingly being recognized as critical for proper spatiotemporal gene expression, particularly in neurons. These regulatory events are governed by a large number of transacting factors found in neurons, most notably RNA-binding proteins (RBPs) and micro-RNAs (miRs), which bind to specific cisacting elements or structures within mRNAs. Through this binding mechanism, trans-acting factors, particularly RBPs, control all aspects of mRNA metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 212 publications
(324 reference statements)
5
118
0
2
Order By: Relevance
“…Our data analysis identified a cluster of RBPs that are expressed in both brain and in human islets. This cluster includes members of the Elavl, Nova, and Rbfox families, which have been implicated in neuronal physiology and disease (28,(31)(32)(33)(34)(35). We found that Elavl4 and Nova2 are required for beta cell survival, and their depletion leads to activation of the intrinsic pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 77%
“…Our data analysis identified a cluster of RBPs that are expressed in both brain and in human islets. This cluster includes members of the Elavl, Nova, and Rbfox families, which have been implicated in neuronal physiology and disease (28,(31)(32)(33)(34)(35). We found that Elavl4 and Nova2 are required for beta cell survival, and their depletion leads to activation of the intrinsic pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 77%
“…They are about 10 to 15 times bigger than the average Drosophila gene, have several promoters, and, most prominently, have unusually long 3= UTRs (64,65). Complex transcriptional control and extended UTRs are also found in Hu genes, suggesting that elaborate regulation of expression of ELAV/Hu genes is a key feature of their functioning (66).…”
Section: Discussionmentioning
confidence: 99%
“…22 HuD is a member of neuronal Hu proteins and functions via binding to adenine/uridine-rich elements (AREs) on target mRNAs. 23 Our previous work revealed that the function of HuD is not only target mRNA stabilization but also the translation stimulation of cap-poly(A) mRNA. 24 We also showed that HuD can associate with cap-binding eIF4F complex through the direct interaction with eIF4A and the stimulatory effect of HuD on translation depends on the binding of HuD to eIF4A and poly(A) tail.…”
Section: The Molecular Mechanism Of Translation Repression By Miriscmentioning
confidence: 99%